Filial Love and Fear in “Más allá de la vida y la muerte” by César Vallejo - García, Mara L. (Espergesia, 2017)
In César Vallejo the inadmissible and the surprise are present to increase the atmosphere of fear and horror in the character and in the reader. Another element present in the author of The Black Heralds is the fantastic. The reader is immersed in a real textual space where the strange not only surprises, but also bursts into the normal Andean realm. In Vallejo, the supernatural invades the real realm and, from then on, the character experiences terror and horror at the presence of abnormal events and the specter of the dead mother. The feminine role in Vallejo is very important since it is this one that opens the door to the unusual and it is the instrument for the inadmissible to take place in normal space. Vallejo uses the fantastic to highlight the importance of the mother as a provider of physical and spiritual food even until after death. For these purposes we will use David Roas´s critical studies and of other scholars of fear and fantasy because of their relevance to this research.